2012
DOI: 10.1126/scisignal.2002739
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Activation of mTOR Complex 1 Is Sufficient to Cause Hepatocellular Carcinoma in Mice

Abstract: The mammalian target of rapamycin (mTOR) complex 1 (mTORC1) is a nutrient sensitive protein kinase that is aberrantly activated in many human cancers. However, whether dysregulation of mTORC1 signaling in normal tissues contributes to cancer risk is unknown. Here, we focused on hepatocellular carcinoma because it is a cancer with clear links to environmental factors that affect mTORC1, including dietary influences. Genetic ablation of the mTORC1 inhibitory component Tsc1 results in constitutively elevated mTOR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
148
3
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 167 publications
(162 citation statements)
references
References 103 publications
10
148
3
1
Order By: Relevance
“…Consistent with this notion, activation of AKT has been found in 40%-60% of human HCC samples (12) and is a risk factor for early recurrence and poor prognosis (13). More importantly, recent studies using knockout mice showed that mTOR activation was sufficient to cause HCC in rodent models (14), indicating the pivotal role of mTOR signaling in HCC. The allosteric mTORC1 inhibitor RAD001/everolimus has been tested in a randomized, placebo-controlled phase III clinical trial in patients with advanced HCC who failed sorafenib (EVOLVE-1; ref.…”
Section: Introductionsupporting
confidence: 50%
“…Consistent with this notion, activation of AKT has been found in 40%-60% of human HCC samples (12) and is a risk factor for early recurrence and poor prognosis (13). More importantly, recent studies using knockout mice showed that mTOR activation was sufficient to cause HCC in rodent models (14), indicating the pivotal role of mTOR signaling in HCC. The allosteric mTORC1 inhibitor RAD001/everolimus has been tested in a randomized, placebo-controlled phase III clinical trial in patients with advanced HCC who failed sorafenib (EVOLVE-1; ref.…”
Section: Introductionsupporting
confidence: 50%
“…In another study done by Villanueva et al [38] that aimed at analyzing 314 HCC samples for mutation detection, DNA copy number changes, determination of mRNA levels and protein by immunohistochemistry reported that PTEN the tumor suppressor that inhibits the mTOR pathway, is inactivated in around half of HCC tumors. Furthermore, the importance of mTOR in hepatocarcinogenesis has been shown in a mouse model with a liver-specific knockout of the negative regulator of mTOR, tuberous sclerosis complex 1 (Tsc1) resulted in chronic mTOR activation and led to the sporadic and sequential development of histological features associated with HCC [39]. Taken together, blockade of PI3K/AKT/mTOR signaling appears to be an attractive therapeutic strategy in HCC.…”
Section: Pi3k/akt/mtor Pathwaymentioning
confidence: 99%
“…In experimental models, knockout models of various proteins required for autophagy demonstrated increased cancers, including spontaneous hepatocellular carcinoma. [32][33][34][35] …”
Section: Prevention Of Tumorigenesismentioning
confidence: 99%